2007
DOI: 10.1177/1070496507310740
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Natural Resource Management

Abstract: This article explores the reasons why community-based natural resource management is not necessarily a panacea. One reason may be that the communitarian benefits associated with social capital formation generally focus on the structural approach (e.g., network connections, group size) and too rarely take into consideration the underlying cultural context in which these relationships are embedded. Using Bourdieu's seminal framework for the different forms of capital (social, cultural, and symbolic), it indeed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(70 citation statements)
references
References 58 publications
2
64
0
4
Order By: Relevance
“…Through such research, social capital has been usefully conceptualized as comprising three dimensions: 1) bonding social capital, which includes the horizontal connections found within a group, (also referred to as 'strong ties'); 2) bridging social capital, involving the horizontal links that are found connecting or bridging individuals who belong to distinct groups ('weak ties'); and 3) linking social capital, described as vertical ties to sources of power and finance developed among social actors involved in shared tasks to improve the common good (Grootaert et al 2003;Sabatini 2009). While many studies have identified the positive contributions of different forms of social capital to communities, others have identified the 'dark side' of social capital (Rubio 1997;Ballet et al 2007). For instance, 'network closure' (Granovetter 1973;Burt 2000) can result from bonding social capital leading to increased homogeneity of beliefs, behaviour, and knowledge within the network while reducing exchange with outsiders (see for example, Barnes-Mauthe et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Through such research, social capital has been usefully conceptualized as comprising three dimensions: 1) bonding social capital, which includes the horizontal connections found within a group, (also referred to as 'strong ties'); 2) bridging social capital, involving the horizontal links that are found connecting or bridging individuals who belong to distinct groups ('weak ties'); and 3) linking social capital, described as vertical ties to sources of power and finance developed among social actors involved in shared tasks to improve the common good (Grootaert et al 2003;Sabatini 2009). While many studies have identified the positive contributions of different forms of social capital to communities, others have identified the 'dark side' of social capital (Rubio 1997;Ballet et al 2007). For instance, 'network closure' (Granovetter 1973;Burt 2000) can result from bonding social capital leading to increased homogeneity of beliefs, behaviour, and knowledge within the network while reducing exchange with outsiders (see for example, Barnes-Mauthe et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Pero la promesa central del capital social común a todas las definiciones es que la inversión de las personas y colectivos en relaciones sociales se verá retribuida en otras formas de capital y en el consecuente aumento en sus oportunidades y capacidades para lograr sus metas (Portes, 1998). Esta hipótesis se ha hecho extensiva también al ámbito del manejo de los recursos naturales y la sustentabilidad ambiental (Pretty y Ward, 2001;Ballet, Sirven y Requiers-Desjardins, 2007). En consecuencia, mayores niveles de capital social (conectividad) estarían asociados a un mejor desempeño en el manejo de sistemas socioecológicos.…”
Section: Capital Social Para Comprender El Funcionamiento De Un Sisteunclassified
“…Models are seductively easy to view as 'reductionist propositions [that]…consist in expressing the phenomenon to be explained in more fundamental terms' (Maturana 1988). This kind of interpretation is particularly appealing to policy-makers who wish to avoid the complex, valuebased nature of governance decisions (Lyons 2005), and is apparent in the development of misleadingly prescriptive 'one size fits all' governance strategies (Ballet et al 2007;Pannell 2008;Kenward et al 2011). Any given approach to modelling complex systems contains within it assumptions, often hidden, about the basic dynamics of these systems, and the consequences of these assumptions for understanding and management need to be carefully considered.…”
Section: Top-down Modellingmentioning
confidence: 99%
“…Land use is governed by legal concepts of ownership and entitlement, concepts of distributive justice, patterns of authority, cultural, aesthetic and religious values and individual decision-making. The potential changes in land use as these conditions vary are myriad, reflecting complex dynamics within and between social and environmental systems (Hanna and Folke 1996;Röling 1997;Ostrom et al 1999;Ballet et al 2007). Indeed, these inter-relationships have motivated the development and widespread adoption of socio-ecological systems theory (e.g.…”
Section: Introductionmentioning
confidence: 99%